2019
DOI: 10.3390/ma12040680
|View full text |Cite
|
Sign up to set email alerts
|

Unified Theory for Flexural Strengthening of Masonry with Composites

Abstract: Recent calamitous events have shown the fragility of the existing masonry buildings. Many of them are heritage structures, such as churches and monumental buildings. Therefore, optimized strengthening strategies are necessary. Experimental studies performed on masonry elements strengthened with composite systems have shown the performance of these materials. However, further development is necessary to optimize the intervention strategies. In fact, due to the lack of general validity models, the design is usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…For this work, no tension was assumed. When the strengthening system is included, the effect of the tensile strength of masonry on flexural capacity becomes certainly negligible [26]. In compression, the model suggested by the Eurocode, EC6, was used, [27].…”
Section: Mechanical Model Of Masonrymentioning
confidence: 99%
See 2 more Smart Citations
“…For this work, no tension was assumed. When the strengthening system is included, the effect of the tensile strength of masonry on flexural capacity becomes certainly negligible [26]. In compression, the model suggested by the Eurocode, EC6, was used, [27].…”
Section: Mechanical Model Of Masonrymentioning
confidence: 99%
“…These values are sufficient to calculate the homogenized stress-strain relationship of composite as shown in figure 1 (b), (c) and (d), (i.e. modules E1, E2, E3 and the homogenized cracking stress σ * CR) [26]. The behavior in compression of the strengthening system has been neglected.…”
Section: Mechanical Model Of Compositementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several authors observed good performances in practical applications [14][15][16][17][18][19]. More studies, however, are required to better understand the behavior of composite material on the structural response of strengthened masonry elements [20][21][22], both in terms of flexural [23][24][25] and shear performance [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…odern strengthening strategies can be performed to improve the structural capacity of several types of structures [1,2]. For masonry buildings strengthening strategies can be applied to improve different aspects [3,4].…”
Section: Introductionmentioning
confidence: 99%